Aquaporin 9 Represents a Novel Target of Chronic Liver Injury That May Antagonize Its Progression by Reducing Lipotoxicity. (6th October 2021) - Cheng, Quancheng; Ding, Huiru; Fang, Jinyu; Fang, Xuan; Liu, Huaicun; Wang, Jianwei; Chen, Chunhua; Zhang, Weiguang
Abstract : In recent years, chronic liver injury has become a common disease that harms human health. Its clinical manifestations are hepatic steatosis and secondary chronic steatohepatitis, which can quickly transform into liver fibrosis and cirrhosis if not treated in time. Therefore, this study is aimed at searching for new therapeutic targets of chronic liver injury and clarifying the molecular mechanisms of the new targets involved in chronic liver injury. After aquaporin 9 was identified as a target by proteomics, Aqp9 -/- mice were constructed using the CRISPR/Cas9 system. Biochemical and morphological tests were used to verify the effect of Aqp9 knockout on early chronic liver injury. Proteomics, molecular biology, and morphology experiments were used to screen and verify the effects of Aqp9 knockout on its downstream pathway. Through the above experiments, we demonstrated that aquaporin 9 could be used as an intervention target for antagonizing the development of early chronic liver injury and its gene knockout affected downstream inflammation, oxidative stress, apoptosis, and pyroptosis by alleviating hepatic lipotoxicity.